PEMBELAJARAN KIMIA MENGGUNAKAN REAL-LAB DAN VIRTUAL-LAB DITINJAU DARI KEMAMPUAN AWAL TERHADAP HASIL BELAJAR LAJU REAKSI - Anggita Efa Rizki; Feri Andi Syuhada (Universitas Negeri Medan, 2020)
The objective of this research is to determine the differences and interactions of student learning outcomes with real laboratories and virtual laboratories using the Guided Inquiry model. This research uses an experimental method with a 2x2 factorial design. Samples were taken by purposive sampling. Data collection using test techniques for cognitive achievement. The data analysis technique uses two-way ANAVA technique. The research results by media factors (A) known Fhit>Ftable (48.37>4.08) then Ho is rejected means that there are differences in student learning outcomes with real laboratories and virtual laboratories using Guided Inquiry models. In the initial ability factor (B) known Fhit>Ftable (14.61>4.08) then Ho is rejected means that there are differences in learning outcomes of students with high and low initial ability. In the interaction (AxB) it is known that Fhit>Ftable (33.9>4.08) then Ho is rejected, meaning there is an interaction between students with real laboratories and virtual laboratory with different initial abilities towards learning outcomes.